2015
DOI: 10.1126/scitranslmed.3010297
|View full text |Cite
|
Sign up to set email alerts
|

The long-acting integrase inhibitor GSK744 protects macaques from repeated intravaginal SHIV challenge

Abstract: Daily preexposure prophylaxis (PrEP) with Truvada is a proven HIV prevention strategy; however, its effectiveness is limited by low adherence. Antiretroviral drug formulations that require infrequent dosing may increase adherence and thus PrEP effectiveness. We investigated whether monthly injections of a long-acting formulation of the HIV integrase inhibitor GSK1265744 (GSK744 LA) prevented simian/human immunodeficiency virus (SHIV) infection by vaginal challenge in macaques. Female pigtail macaques (n = 12) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
66
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 22 publications
(55 reference statements)
6
66
0
Order By: Relevance
“…The relevance of PTM vaginal physiology has allowed researchers to assess in this species the impact of factors such as coinfections and contraceptive use on susceptibility to vaginal infection [29*,30], and to evaluate modalities to prevent vaginal virus transmission, including microbicides and other pharmacologic interventions [3134], all while accounting for menstrual cycle phases [30,35,36*–38]. However, within-species comparisons of intravaginal and intrarectal challenges using PTMs may be confounded by the higher levels of baseline immune activation associated with elevated intestinal permeability and microbial translocation in the absence of infection in PTMs when compared with RMs [39].…”
Section: Nhp Host Speciesmentioning
confidence: 99%
“…The relevance of PTM vaginal physiology has allowed researchers to assess in this species the impact of factors such as coinfections and contraceptive use on susceptibility to vaginal infection [29*,30], and to evaluate modalities to prevent vaginal virus transmission, including microbicides and other pharmacologic interventions [3134], all while accounting for menstrual cycle phases [30,35,36*–38]. However, within-species comparisons of intravaginal and intrarectal challenges using PTMs may be confounded by the higher levels of baseline immune activation associated with elevated intestinal permeability and microbial translocation in the absence of infection in PTMs when compared with RMs [39].…”
Section: Nhp Host Speciesmentioning
confidence: 99%
“…In low dose challenge models designed to more closely mimic HIV-1 transmission in humans, macaques administered CAB LA as PrEP were completely protected from repeated intrarectal [14] or intravaginal [15] SHIV162P3 challenges. Additionally, in a female rhesus macaque model utilizing Depo-Provera to thin the cervicovaginal epithelium to increase the probability of infection, CAB LA protected 6 of 8 female macaques from repeated high-dose intravaginal challenges [16].…”
Section: Introductionmentioning
confidence: 99%
“…Median individual tissue:plasma drug concentration ratios ranged from 16 to 25% in the female genital tract and were 8% in rectal tissue in men suggesting that at the dose tested the formulation would fall short as a PrEP agent. Furthermore, a recent study conducted in rhesus macaques showed that two IM doses 1 month apart protected eight out of eight animals from multiple rectal exposures to simian/human immunodeficiency virus (SHIV), while all eight animals receiving placebo injections acquired infection [147149]. …”
Section: Introductionmentioning
confidence: 99%